Factors affecting in vitro embryo production: insights into dromedary camel - Adel R. Moawad; Ibrahim M. Ghoneim; Gamal M. Darwish; Magdy R. Badr; Diya A. El-Badry; Abou Bakr A. EL-Wishy (The Korean Society of Animal Reproduction and Biotechnology, 2020)
The Dromedary camel (Camelus dromedaries) is an important species because of its ability to produce good quality meat, milk, and fibers under harsh environmental conditions. Camels are also crucial for transportation, racing, and as draft animals in agriculture. Therefore, dromedary camels play a critical role in the economy for millions of people living in the arid part of the world. The inherent capability of camels to produce meat and milk is highly correlated with their reproductive performance. Compared with other domestic species, the reproductive efficiency in camelids is low. Although recent reproductive technologies such as in vitro fertilization (IVF) and somatic cell nuclear transfer (SCNT) have been successfully applied to camelids and the birth of live offspring following these technologies has been reported; in vitro embryo production (IVP) has lagged in this species. The development of the IVP system for dromedary camels may be a useful tool for the genetic improvement of this species. IVP in farm animals includes three main steps; in vitro maturation (IVM) of an oocyte, IVF of a matured oocyte, and in vitro culture (IVC) of fertilized oocyte up to the blastocyst stage. This review aims to summarize various factors that influence oocyte quality, IVM, and in vitro embryo development in dromedary camel.